Cutting efficiency of different dental diamond rotary instruments for sectioning monolithic zirconia and lithium disilicate crowns - Sary Borzangy; Rayan Hassan Bahabri; Abdulrahman Ahmad Alsani; Ahmed Yaseen Alqutaibi; Mohammed Ahmed Alghauli; Mohammed H. AbdElaziz (BMC, 2024)
Abstract Background The aim of this study was to determine the cutting efficiency of different diamond rotary instrument types for sectioning monolithic zirconia and lithium disilicate anatomical crowns. Materials and methods The study used 30 diamond rotary instruments divided into three groups: Zirconia cutting diamond bur (White Z), super coarse grit diamond bur (KBlack), and medium coarse grit diamond bur (KBlue); Two subgroups were assigned based on the crown materials including monolithic zirconia (5YSZ) and lithium disilicate (e.max) ceramics. The cutting efficiency was assessed by measuring the time required to fully section the crowns, followed by scanning electron microscopy (SEM) and energy-dispersive spectroscopy (EDS) of the dental burs before use and after every sectioned crown. A three-way ANOVA examined the effects of bur type, material type, and sectioning stage. If interaction exists, one-way ANOVA was used to compare the different subgroups, followed by the Tukey post hoc test. The significance level was assigned at α ≤ 0.05. Results The results exhibited various cutting efficiencies among diamond rotary instruments and ceramic crown materials. White Z demonstrated superior cutting efficiency of zirconia crown compared with KBlack and KBlue for the first cutting cycles (p ≤ 0.05); the results tend to be more comparable at the third cutting cycle. However, the super coarse diamond bur exhibited higher efficiency in cutting lithium disilicate crowns than white Z and KBlue burs through all three cutting cycles(p ≤ 0.05). The diamond bur-cutting efficiency diminished after each use, irrespective of the bur type or the crown material (p ≤ 0.05); this was represented by the reduction of carbon and increased nickel matrix ratio after each bur usage. Conclusion White Z diamond bur showed higher cutting efficiency of zirconia in the first two cutting cycles; super coarse diamond bur is more efficient for cutting lithium disilicate crown in all of the cutting cycles. The amount of diamond on the burs reduced after each use, with no great impact on the material type when sectioning lithium disilicate and 5YSZ crowns. Clinical significance This study provides valuable insights for dental practitioners in selecting the appropriate diamond rotary instrument for crown sectioning. Practitioners can minimize the risk of damage and reduce the time required for crown removal, improving patient outcomes.